2015
DOI: 10.3109/19396368.2015.1044135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymoquinone on testicular structure and sperm production in male obese rats

Abstract: Thymoquinone (TQ) is a phytochemical compound found in the plant Nigella sativa. It has antioxidant and anti-cancer effects. This study investigated the effects of TQ on obesity and testicular structure of high-fat-diet (HFD) fed rats. Obese control (OC) and obese thymoquinone (OT) groups were fed a special diet containing 40% of total calories from fat. Non-obese control (NC) and non-thymoquinone (NT) groups were fed a standard diet for nine weeks. Then, intraperitoneal TQ injections were carried out to the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…22 Atrophied seminiferous tubuli were also observed in HFD treated rats associated disconnection of the degenerated STs from the interstitial wall with increased area of the connective tissue and remarkable apoptotic activity in Leydig and Sertoli cells. 9 Vacuolar alterations in seminiferous tubules, spermatogenic cell dysfunction, and increased apoptosis of spermatogenic cells in testicular tissue was also observed in HFD treated rats. 23 Currently, many herbal medicines therapeutic available been recommended for the treatment of obesity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…22 Atrophied seminiferous tubuli were also observed in HFD treated rats associated disconnection of the degenerated STs from the interstitial wall with increased area of the connective tissue and remarkable apoptotic activity in Leydig and Sertoli cells. 9 Vacuolar alterations in seminiferous tubules, spermatogenic cell dysfunction, and increased apoptosis of spermatogenic cells in testicular tissue was also observed in HFD treated rats. 23 Currently, many herbal medicines therapeutic available been recommended for the treatment of obesity.…”
Section: Discussionmentioning
confidence: 88%
“…8 Nigella sativa enhance fertility by means of increasing the healthy sperm number and preventing sperm anomalies in HFD fed rats. 9 Cinnamon significantly reduced the cholesterol, triglycerides, and low-density lipoprotein levels and increased high-density lipoprotein in rats fed with a high cholesterol diet "HCD" and improved the disorganized and shrinking of the seminiferous tubules of those received only the HCD. 10 Eurycoma longifolia "EL" (publically known as Tongkat Ali) is a herbal medicinal plant found in South-East Asia, It is a small rain forest flowering, un-branched, medium-sized slender shrub.…”
Section: Introductionmentioning
confidence: 98%
“…G omez-Elías et al (2019) found that animals fed HFD recorded an increase in the body weight, the amounts of gonadal fat and cause hypercholesterolemia and decrease sperm count. Diets riche in cholesterol increased germ cell apoptotic activity, of the Leydig, Sertoli, and peritubular myoid cells, and affect the main steps in sperm development (Tüfek et al, 2015;Sim on et al, 2017). Pinto-Fochi et al (2016) found that HFD reduces the functional capacity of Leydig cells and induces hypoandrogenism.…”
Section: Introductionmentioning
confidence: 99%
“…Thymoquinone, which is one of the most important bioactive components of N. sativa and is responsible for its many biological effects, was first synthesised in 1959 and it was reported that thymoquinone exists as a volatile oil in a proportion of 18.4%-24.0% (Ali & Blunden, 2003;Burits & Bucar, 2000;Yüncü, Şahin, Bayat, & İbrahim, 2013). Other analyses have indicated that the concentration of thymoquinone is 52.6 mg/100 g and 20.13 mg/100 g (Tüfek, Altunkaynak, Altunkaynak, & Kaplan, 2015).…”
Section: Nigella Sativamentioning
confidence: 99%